In search of a family: The contribution of art psychotherapy to a collaborative approach with a man residing in a forensic learning disability setting. (19th October 2017) - Caveney, Domanic; Wassall, Shaun; Rayner, Kelly
Abstract : Accessible Summary: Some clients in learning disability services have problems in their relationships with people. Some clients with learning disability have broken the law and live in hospital. For clients in hospital, treatment can be learning about managing behaviour, feelings and relationships. This treatment is given by different professionals. This treatment is important to help stop these clients getting into trouble with the police again. An important part of treatment is to help clients understand their experiences in relationships. This case study is about Oliver, and how psychologists and an art therapist worked together to help him.​ Abstract: Background: Clients with attachment issues are over‐represented in learning disability services. Forensic inpatient services are no exception. Treatment pathways comprise multidisciplinary interventions, and skills‐based treatments are considered vital to recovery and maintenance of prosocial and adaptive behaviour and reduction in risk. An important aspect of treatment is the psychological intervention to enable clients to understand their early experiences and the way this may have impacted on later relationships and behaviour. Without exploring the difficult early lives that many clients in forensic inpatient services have experienced, skills‐based treatments and attempts to facilitate discharge may not be effective. Materials and methods: This case study presents the theoretical background of attachment, autism, learning disability and sexual offending that informed the collaborative multidisciplinary psychological treatment offered to one man with learning disabilities and autism in a secure forensic setting. Results: The introduction of Art Psychotherapy enabled the client to explore his history and the potential internal barriers to his therapeutic progress. Issues of safety and belonging, previously unexplored with this man, were uncovered and these themes were incorporated into his risk formulation and treatment plan. Conclusions: The paper reflects on the specific contribution of Art Psychotherapy in specialist services, and the importance of the collaborative relationship between the Art Psychotherapist and the ward Multi‐Disciplinary Team.